Free Play in the Context of Early Childhood Contextual Learning Strategies - Fitry, Septi Fitriana (Education Specialist, 2023)
The curriculum introduced by the Minister of Education and Culture is known as the "Merdeka" curriculum. This instructional activity involves using white fabric, coloring agents, containers, and water. It was implemented in a research study conducted at Labschool Profesi Guru (PG) Pendidikan Anak Usia Dini (PAUD) Universitas Bengkulu Indonesia in August 2023, focusing on 15 students in class B1 within the theme "Aku Hamba Allah," aiming to evaluate child development in various aspects. The approach used is explanatory qualitative. Results Based on research that early age is the best foundation in developing future life. In addition, early childhood education can optimize children's basic abilities in receiving the educational process at the next age with play. contextual or Contextual teaching and learning (CLT) is the concept of teacher learning that is linked between learning materials and students' real-world situations, and encourages students to make connections between knowledge and its application in their daily lives. New knowledge and skills as he learns. This research method is qualitative, namely; data generated through direct observation activities when children do learning activities. It can be said that the contextual learning strategy at Labschool Profesi Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan Universitas Bengkulu can be implemented well, through play activities with utilizing human-based media in children's knowledge in learning.